Cover Picture: Eur. J. Lipid Sci. Technol. 5∕2019. Issue 5 (3rd May 2019) - Unknown
Abstract : Oxidative Stability, Affective and Descriptive Sensory Properties of Roasted Peanut Flavored with Oregano, Laurel, and Rosemary Essential Oils as Natural Preservatives of Food Lipids Rubén H. Olmedo and Nelson R. Grosso DOI:10.1002/ejlt.201800428 In article number 1800428, Rubén H. Olmedo and co‐workers highlight how the peanut possesses 50% of lipids which makes it susceptible to oxidation processes. The essential oils of oregano, rosemary and laurel present antioxidant activity for the protection of the lipids found in the oxidation model represented by peanuts. These essential oils prolong the shelf life of the peanuts with respect to the control sample without the addition of antioxidants.